THE SCHOOL ENGLISH TEACHERS’ PERCEPTION ON ASSESSMENT TOWARD TEACHING PROGRAM AT UPT’S SPM LABORATORIUM PERCOBAAN BANDUNG - Hanafi Bilmona (STKIP Siliwangi, 2013)
Assessment has recently become one of the new educational issues around Asia Pacific countries. The two reflective questions formulated are: 1) Is assessment new in the educational life of Indonesia? 2) How do we consider our educational quality compared to countries around Asia pacific? These questions urged this study to conduct a research in UPI’s SMP Laboratorium Percobaan Bandung to see the perceptions, planning and management of the school (the headmaster) and the three English teachers as the participants, in terms of their application of the assessment. In a qualitative descriptive method, the interviewing, observation and document analysis have been implemented to collect the data.. As a result, this school and the English teachers are only familiar with the summative assessment, part of assessment which is mainly grading or testing, evaluative, and less informative to identify students’ learning problem and to recommend teachers’ teaching modification and improvement. KEYWORDS: assessment, teachers’ perception and the teaching